2018
DOI: 10.1002/jcla.22571
|View full text |Cite
|
Sign up to set email alerts
|

The analysis of false prolongation of the activated partial thromboplastin time (activator: silica): Interference of C‐reactive protein

Abstract: C-reactive protein interferes with the detection of APTT, especially in STA-R Evolution (activator: silica) system. The increasing in C-reactive protein results in a false prolongation of the APTT (activator: silica), and it is most likely that C-reactive protein interferes the coagulable factor binding of phospholipid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…However, it has been reported that for some APTT reagents, CRP can be a direct cause of a pseudo‐prolongation of APTT. 9 On the other hand, although the AGR showed a negative correlation with ΔAPTT in multiple regression analysis, no significant change was observed even when AGR was changed by ALB addition. This suggests that the AGR does not directly affect the APTT reaction system.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…However, it has been reported that for some APTT reagents, CRP can be a direct cause of a pseudo‐prolongation of APTT. 9 On the other hand, although the AGR showed a negative correlation with ΔAPTT in multiple regression analysis, no significant change was observed even when AGR was changed by ALB addition. This suggests that the AGR does not directly affect the APTT reaction system.…”
Section: Discussionmentioning
confidence: 83%
“…Previous studies have reported that CRP inhibits phospholipids in some APTT reagents and causes a pseudo‐prolongation of APTT. 9 Therefore, in order to investigate whether CRP inhibits phospholipids in the reagent, purified CRP was added to phospholipid added samples and the effects on APTT values were examined. As shown in Figure 3 , sample with plasma and CRP showed a significant prolongation of APTT‐n as compared with to samples without the addition of CRP nor phospholipids.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Conversely, use of anti‐Xa monitoring in addition to APTT may be beneficial in COVID‐19 patients in whom heparin resistance is suspected. APTT readings may be falsely shortened in patients receiving UFH with an elevated C‐reactive protein, dependent upon the chosen assay or high FVIII levels 49 . Anti‐Xa monitoring may therefore be preferable in these patients, which is of relevance to a significant proportion of COVID‐19 patients 50 .…”
Section: Can Anti‐xa Be Helpful To “Detecting” Heparin Resistance?mentioning
confidence: 99%